Comparison of Combined Perineural Injection and Oral Mecobalamin with Oral Mecobalamin Therapy on Sensory Symptom Improvement in Patients with Carpal Tunnel Syndrome - Diah Andini; Masita Masita; Henry Sugiharto; Erial Bahar (GLOBAL HEALTH SCIENCE GROUP, 2026)
Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy, predominantly presenting with sensory symptoms such as numbness and tingling. Conservative therapy with oral mecobalamin is widely used; however, the onset of improvement is often slow. Perineural injection of mecobalamin may provide a faster local effect, but clinical evidence remains limited. This study aimed to evaluate the effectiveness of combined perineural injection and oral mecobalamin compared with oral mecobalamin alone on sensory symptom improvement in CTS patients. This was a comparative interventional study conducted in patients with mild to moderate CTS at Dr. Mohammad Hoesin General Hospital, Palembang. Subjects were divided into two groups: a combination therapy group (perineural injection plus oral mecobalamin) and an oral mecobalamin group. Sensory symptoms were assessed using the Visual Analog Scale (VAS) at baseline, week 2, and week 4. Between-group and within-group comparisons were analyzed using t-tests, while mixed ANOVA was used to evaluate the effects of time and treatment group. Multivariate analysis was performed to identify factors independently associated with sensory symptom improvement. A total of 30 CTS patients were included in this study. There were no significant differences in baseline demographic and clinical characteristics between groups. Mixed ANOVA analysis demonstrated a significant time effect (p < 0.001) and a significant time group interaction, indicating a faster pattern of sensory symptom improvement (VAS score reduction) in the combination group. Multivariate analysis showed that combination therapy, sex, and occupation were independently associated with sensory symptom improvement, with occupation being the most dominant factor. The combination of perineural injection and oral mecobalamin is more effective in accelerating and enhancing sensory symptom improvement compared with oral mecobalamin therapy alone in patients with mild to moderate CTS.